Dirac Nodal Arc Semimetal PtSn4: An Ideal Platform for Understanding Surface Properties and Catalysis for Hydrogen Evolution. (13th August 2019) - Li, Guowei; Fu, Chenguang; Shi, Wujun; Jiao, Lin; Wu, Jiquan; Yang, Qun; Saha, Rana; Kamminga, Machteld E.; Srivastava, Abhay K.; Liu, Enke; Yazdani, Aliza N.; Kumar, Nitesh; et al.
Abstract: Conductivity, carrier mobility, and a suitable Gibbs free energy are important criteria that determine the performance of catalysts for a hydrogen evolution reaction (HER). However, it is a challenge to combine these factors into a single compound. Herein, we discover a superior electrocatalyst for a HER in the recently identified Dirac nodal arc semimetal PtSn4 . The determined turnover frequency (TOF) for each active site of PtSn4 is 1.54 H2  s −1 at 100 mV. This sets a benchmark for HER catalysis on Pt‐based noble metals and earth‐abundant metal catalysts. We make use of the robust surface states of PtSn4 as their electrons can be transferred to the adsorbed hydrogen atoms in the catalytic process more efficiently. In addition, PtSn4 displays excellent chemical and electrochemical stabilities after long‐term exposure in air and long‐time HER stability tests. Abstract : Halbmetall, voll leistungsfähig : Das Dirac‐Halbmetall PtSn4 besitzt eine zweidimensionale Schichtstruktur. Intrinsische, stabile Oberflächenzustände sind in der Pt‐Schicht des PtSn4 ‐Einkristalls vorhanden. Die p‐Orbitale der Pt‐Atome können in diesen robusten Zuständen effizient Elektronen für die Wasserstoffreduktion bereitstellen. PtSn4 ist demnach ein Benchmark‐Elektrokatalysator für die Wasserstoffentwicklung.